2017
DOI: 10.1002/mgg3.269
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcription factors potentially involved in human adipogenesis in vitro

Abstract: BackgroundIncreased adiposity in humans leads to obesity, which is a major risk factor for cardiovascular disease, type 2 diabetes, and cancer. We previously conducted an extensive unbiased in vitro transcriptomic analysis of adipogenesis, using human adipose‐derived stromal cells (ASCs). Here, we have applied computational methods to these data to identify transcription factors (TFs) that constitute the upstream gene regulatory networks potentially, driving adipocyte formation in human ASCs.MethodsWe used Aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 60 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…2j ). ZNF263 is involved in adipogenesis 39 . The Ewing sarcoma RNA binding protein 1 (EWSR1) regulates gene expression, cell signalling, RNA processing and transport.…”
Section: Resultsmentioning
confidence: 99%
“…2j ). ZNF263 is involved in adipogenesis 39 . The Ewing sarcoma RNA binding protein 1 (EWSR1) regulates gene expression, cell signalling, RNA processing and transport.…”
Section: Resultsmentioning
confidence: 99%
“…The process of adipogenesis has been extensively studied and decades of research have reported over a dozen transcription factors to be involved in regulating this process, both in vitro and in vivo [146,147] (Figure 2). The transcription factor Zfp423 plays an essential role in regulating MSC commitment to preadipocytes and its expression remains unchanged during adipogenesis [148,149].…”
Section: Transcriptional Regulation Of Adipogenesismentioning
confidence: 99%
“…Other transcription factors such as LIM only domain protein 3 (LMO3), FOXO1 and zinc finger and BTB domain containing 16 (ZBTB16), have been shown to be highly expressed during human adipogenesis in vitro, suggesting a possible role in promoting this process [174]. In silico analysis of genes that were differentially expressed during human adipogenesis in vitro [174] has identified several other transcription factors with possible roles in adipocyte differentiation [146].…”
Section: Transcriptional Regulation Of Adipogenesismentioning
confidence: 99%
“…Other TFs enriched identified include TCF12, which is part of the canonical Wnt pathway and implicated as a transcriptional repressor in colorectal cancer (Lee et al, 2012). Specificity proteins (Sp1, Sp2, Sp3 and Sp8) which are known to interact with bHLH proteins such as MyoD (Biesiada et al, 1999); and znf263 a zinc-finger TF involved in adipogenesis (Ambele and Pepper, 2017).…”
Section: Transcriptional Profiling Of Developing Paraxial Mesodermmentioning
confidence: 99%